2016
DOI: 10.4067/s0034-98872016000300008
|View full text |Cite
|
Sign up to set email alerts
|

Alteraciones tiroideas en pacientes infectados con el virus de inmunodeficiencia humana

Abstract: Background: Thyroid dysfunction is common among patients infected with human immunodeficiency virus (HIV). (Rev Med Chile 2016; 144: 333-340)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(44 reference statements)
0
1
0
1
Order By: Relevance
“…Similarly, in another recent cross-sectional study in Chile on 127 HIV patients, the authors revealed a prevalence in hypothyroidism (10.2%), followed by hypothyroxinemia (6.29%) and reported only one case of hyperthyroidism. Notably, the thyroid abnormalities biochemically detected were generally asymptomatic [ 17 ]. Conversely, an Italian retrospective study on 6343 PLWH found 113 patients (1.8% of the total) who have received a diagnosis of symptomatic thyroid diseases (10 patients with euthyroid goiter were excluded): 81 of them (71.7%) with hypothyroidism, 21 (18.5%) with hyperthyroidism and 11 (9.7%) with a primary thyroid tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in another recent cross-sectional study in Chile on 127 HIV patients, the authors revealed a prevalence in hypothyroidism (10.2%), followed by hypothyroxinemia (6.29%) and reported only one case of hyperthyroidism. Notably, the thyroid abnormalities biochemically detected were generally asymptomatic [ 17 ]. Conversely, an Italian retrospective study on 6343 PLWH found 113 patients (1.8% of the total) who have received a diagnosis of symptomatic thyroid diseases (10 patients with euthyroid goiter were excluded): 81 of them (71.7%) with hypothyroidism, 21 (18.5%) with hyperthyroidism and 11 (9.7%) with a primary thyroid tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos estudios han sugerido que la prevalencia de enfermedad tiroidea en pacientes con VIH es del 17%. (Báez, et al 2016). Por lo cual, se buscó determinar la relación de disfunción tiroidea en pacientes infectados por VIH con TARGA asociándolo con la duración de la terapia, recuento de células CD4 y carga viral, ya que en la actualidad las tendencias metabólicas progresivas en el mundo asociado al riesgo de cambios metabólicos causados por la terapia antirretroviral se han considerado como factor exclusivo para la disfunción tiroidea, de igual forma la ausencia de terapia (Draenert, 2015).…”
Section: Introductionunclassified